2015
DOI: 10.1038/ncomms8636
|View full text |Cite
|
Sign up to set email alerts
|

Dichroic spin–valley photocurrent in monolayer molybdenum disulphide

Abstract: The aim of valleytronics is to exploit confinement of charge carriers in local valleys of the energy bands of semiconductors as an additional degree of freedom in optoelectronic devices. Thanks to strong direct excitonic transitions in spin-coupled K valleys, monolayer molybdenum disulphide is a rapidly emerging valleytronic material, with high valley polarization in photoluminescence. Here we elucidate the excitonic physics of this material by light helicity-dependent photocurrent studies of phototransistors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
154
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(157 citation statements)
references
References 42 publications
3
154
0
Order By: Relevance
“…[118] By circularly polarized optical pumping, ( Vertical heterojunction) and transfer photovoltaic 3.1 NA NA NA [106] spin-valley coupled polarization can be generated, [119] which has been observed in optoeletronic devices based on MoS2 [120] and WSe2. [121,122] It should be of great significance to introduce spin-polarization and valley-polarization in photodetectors based on junctions of TMDCs.…”
Section: Discussionmentioning
confidence: 99%
“…[118] By circularly polarized optical pumping, ( Vertical heterojunction) and transfer photovoltaic 3.1 NA NA NA [106] spin-valley coupled polarization can be generated, [119] which has been observed in optoeletronic devices based on MoS2 [120] and WSe2. [121,122] It should be of great significance to introduce spin-polarization and valley-polarization in photodetectors based on junctions of TMDCs.…”
Section: Discussionmentioning
confidence: 99%
“…The sign of the Hall voltage could be controlled by the helicity of the light, whereas there was no effect detectable for linearly polarized light or (inversion-symmetric) bilayer devices. Other studies demonstrated a valley dependent photodetector in CVD grown MoS 2 [115] and the generation of spin-valley-coupled circular photogalvanic currents in WSe 2 [116]. Zhang et al [65] fabricated a chiral light-emitting transistor by forming a multi-layer WSe 2 p-n junction using electric double layer gating.…”
Section: Valleytronicsmentioning
confidence: 99%
“…This property enables selectively pumping + K (− K ) valley with left (right) hand circular light excitations to create an imbalanced carrier population between two valleys. Realizing such net valley polarization is an essential step for developing valleytronic devices . Resulted from the opposite selection rules of two valleys, controlling valley polarization in mono‐layer TMDs by optical helicity is achievable.…”
mentioning
confidence: 99%